Interim governments and the stability of peace - Strasheim, Julia (2017)
After intrastate armed conflict, what properties of interim governments increase the stability of post-interim peace? Previous research on interim governments has often relied on evidence gathered through under-theorized and non-comparative case studies, making findings difficult to generalize. The literature also tends to concentrate on studying the institutional designs of interim governments as explanatory variables, while neglecting the variety of reforms such governments implement. To address these shortcomings, this dissertation develops a bargaining model on how interim governments increase the stability of post-interim peace by mitigating credible commitment problems of warring parties. This bargaining model theorizes that both the institutional designs of interim governments – whether or not they include power-sharing arrangements for the warring parties, as well as whether or not international actors assume political authority during interim rule – as well as their reform processes affect the stability of post-interim peace. It argues for two reform processes in particular. First, it holds that interim governments that implement reforms to integrate the parallel political and military institutions of warring parties (such as shadow governments and non-statutory armed forces) should increase the stability of peace. Second, it argues that interim governments that allow for the participation of unarmed actors in reform processes – such as civil society representatives – should increase the stability of post-interim peace. The dissertation tests these hypotheses by using a mixed-method research design that combines statistical survival analysis with process-tracing in and a comparative analysis of three case studies. In the quantitative analysis, it relies on a novel data set of a sample of all interim governments that followed at least one year of intrastate armed conflict since 1989, and that terminated by 2012. The qualitative case studies, selected under a most-similar system design, include the interim governments of Nepal (2006-2008), Angola (1991-1992), and Cambodia (1991-1993). In sum, results from both quantitative and qualitative analyses show that the reforms implemented by interim governments provide for a better explanation for long-term peace as compared to the institutional designs of such governments. In particular, the dissertation finds strongest support for hypothesis H3 on the integration of parallel political and military institutions into the authority of interim governments. The dissertation concludes by discussing policy implications and avenues for future research.